El negocio jurídico de prendar acciones - López Restrepo, Julieta (2023)
This article is part of a research project on pledges and security interests. It covers a wide range of topics in both civil and commercial law because there are many different ways to secure the performance of an obligation, an d security interests may be taken on any type of property. In practice, pledging and security interests are difficult subjects to understand, not only because of the conflict of laws they generate, but also because security instruments themselves represent various political and economic rights claimed by the entities that own them or have an interest in them. This article’s main objective is to analyze security interests and pledging in Colombia, and to determine whether current legislation is sufficient to appropriately regulate all types of proprietary security interests. Finally, a few recommendations will be discussed.